MEMBANGUN KESADARAN BUNYI ANAK TUNARUNGU MELALUI PEMBELAJARAN BINA PERSEPSI BUNYI DAN IRAMA DI SEKOLAH - Hermanto, Hermanto (MAJALAH ILMIAH PEMBELAJARAN, 2010)
Loss of function of hearing someone cause their inability to capture information through hearing. Deaf is not just the loss of function hearing someone, but far from it deafness cause functional limitation of understanding and ability to perceive something. Deafness also lead to the ability of a person is not able to speak well. For that to enhance the ability of children with hearing it is necessary to attempt to build awareness of sounds in order for them to follow verbal communication better. The building awareness of these sounds can be provided through community development learning perception of sound and rhythm. Learning is certainly not enough to just be given by a teacher BPBI course, but what about support from fellow teachers at the school in building a sound awareness of this can be done in synergy or coordination. With the correct and appropriate learning, and has the support of all components of the school, then build awareness of sound, especially in the lower classes would be achieved as the destination set as the purpose of BPBI instructional.